Financial Performance Assessment of Islamic Commercial Banks Post Covid-19: Mediation Role of Profitability - yanti, evi maulida; Nasution, Muhammad Syafril; Rusydi; Nurfaza, Arina; Jamaluddin (Jurnal Manajemen (Edisi Elektronik), 2025)
This study is a quantitative study using data in the form of financial reports of Islamic Commercial Banks in Indonesia after Covid-19. The report data used from 2021 to 2023 were collected through the official websites of each bank and the Financial Services Authority (www.ojk.go.id). In assessing the financial performance of Islamic Commercial Banks, there are several variables used in this study, including: intervening variables, namely profitability, dependent variables, namely non-performing financing, and independent variables, namely: capital adequacy ratio and operating expenses to operating income. The results of the study indicate that the capital adequacy ratio and operating expenses to operating income have no relationship to return on assets, capital adequacy ratio and return on assets also have no relationship to non-performing financing, while operating expenses to operating income have an effect on non-performing financing. Based on the Sobel test conducted, it can be concluded that return on assets is not able to mediate the capital adequacy ratio and operating expenses to operating income against non-performing financing.